2005
DOI: 10.1007/s00442-005-0294-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional differences and leaf acclimation of climbing plants and the associated vegetation in different types of an Andean montane rainforest

Abstract: Climbing plants are known to play an important role in tropical forest systems, but key features for their distribution are only partly understood. Investigation was carried out to find if climbers differ from self-supporting vegetation in their adjustment of leaf parameters over a wide variety of light regimes in different forest types along an altitudinal gradient. Relative photon flux density (PFDrel) was assessed above 75 pairs of strictly linked climbers and supporting vegetation on seven plots between 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 56 publications
11
27
0
Order By: Relevance
“…Our findings confirmed and expanded upon previous research from individual sites and regions (Castro-Esau et al 2004;Castro-Esau et al 2006;Salzer et al 2006;Zhang et al 2006;Sanchez-Azofeifa et al 2009;Zhu & Cao 2010;Kazda, Chapter 22 in this volume). In particular, we found that lianas maintain an average 14.5% and 16.7% higher concentrations of chemicals responsible for light capture, carbon fixation, and foliar metabolism.…”
Section: Introductionsupporting
confidence: 81%
“…Our findings confirmed and expanded upon previous research from individual sites and regions (Castro-Esau et al 2004;Castro-Esau et al 2006;Salzer et al 2006;Zhang et al 2006;Sanchez-Azofeifa et al 2009;Zhu & Cao 2010;Kazda, Chapter 22 in this volume). In particular, we found that lianas maintain an average 14.5% and 16.7% higher concentrations of chemicals responsible for light capture, carbon fixation, and foliar metabolism.…”
Section: Introductionsupporting
confidence: 81%
“…These growth characteristics indicate the high capacity of lianas to acclimatize to light and supports the hypothesis that lianas share attributes of both lightdemanding and shade-tolerant species (Schnitzer and Bongers 2002). The high leaf acclimation potential of lianas has been reported in several studies (Avalos and Mulkey 1999;Salzer et al 2006;Sanches and Válio 2008).…”
Section: Discussionsupporting
confidence: 66%
“…The leaves of lianas tend to be smaller and thinner and have higher levels of nitrogen, phosphorus and potassium per unit area than do the leaves of their host trees. 8 These leaf traits characterize phenotypically plastic species that are able to respond strongly to fertilization, be it through nutrient deposition or rising CO 2 concentrations, to achieve rapid growth rates.…”
Section: Putative Mechanisms For Neotropical Liana Increasesmentioning
confidence: 99%